Asiatic Acid Induces Endoplasmic Reticulum Stress and Activates the Grp78/IRE1α/JNK and Calpain Pathways to Inhibit Tongue Cancer Growth - Li, Jialin; Chen, Kan; Huang, Jianhua; Chu, Dongqing; Tian, Miaomiao; Huang, Keqiang; Ma, Chunyu (Frontiers in Pharmacology, 2021)
Asiatic acid (AA) has been shown to induce apoptotic death in a range of cancers, but the mechanisms whereby it can inhibit tongue cancer growth have yet to be clarified. Herein, we explored the effects of AA on tongue cancer cells and found that it induced their apoptotic death in vitro and in vivo, while additionally impairing xenograft tumor growth in vivo. From a mechanistic perspective, AA treatment was associated with increases in levels of calcium and the calcium-dependent protease calpain, and it further induced endoplasmic reticulum (ER) stress and consequent Grp78-related IRE1α and JNK phosphorylation, ultimately driving caspase-3 activation and apoptotic death. Together, these results highlight AA as a promising tool for the therapeutic treatment of tongue cancer in clinical practice.